Soil ecological restoration applying biochar (charcoal) and its effects on the Medicago sativa production (2015)
ln the province of Chimborazo, Riobamba canton, and San Pedro of Abras neighborhood (Ecuador) an ecological restoration on the soil was studied by applying different levels of charcoal (10, 20 and 30 tha") and its effect on the alfalfa Medicago sativa forage production was evaluated, under a block design completely randomized. The best results were obtained by applying 30 t.ha'“ charcoal, in this way: In the first cut was reached the lowest flowering time occurrence (40,50 days) the highest basal coverage (39,35%) and highest aerial coverage (86,0%) the best height (87,98 cm) and the highest numbers of leaves per stem (103,45) and above all the highest forage production, both in green material (15,80 t.FV"ha" cut) as in dried one (33,38 t.MS'“ha'l year). In the second cut was achieved the best basal cover (86,55%) and aerial (95,42%) as well the largest production in green forage (15,92 t.ha'lcut), and in dry matter (33,70t.MS'lha'l year). The economical analysis registered the highest profitability with the 30 t.ha'“ of charcoal cost-benefit of$ 1,63.lt’s recommended to apply in Medicago sativa 30 t.ha" of charcoal, because with it a larger amount of green forage by cut was obtained and improved the soil quality, which will guarantee to obtain economic returns that benefit the agricultural and livestock producers.